2016
DOI: 10.1007/s00737-016-0622-8
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of chronic stress and mental health concerns among urban Indigenous women

Abstract: We measured stress, depression and post-traumatic stress disorder (PTSD) levels of urban Indigenous women living with and without HIV in Ontario, Canada, and identified correlates of depression. We recruited 30 Indigenous women living with HIV and 60 without HIV aged 18 years or older who completed socio-demographic and health questionnaires and validated scales assessing stress, depression and PTSD. Descriptive statistics were conducted to summarize variables and linear regression to identify correlates of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 91 publications
(157 reference statements)
0
14
0
Order By: Relevance
“…Elsewhere, we report on strategies to mitigate these limitations including further privileging Indigenous knowledge ( McKenzie, Varcoe, Browne, & Ford-Gilboe, 2018 ). Some women enrolled but were unable participate, reflecting the extreme economic deprivation and high levels of trauma many Indigenous women face ( Benoit et al, 2016 ; Daoud et al, 2013 ; Kubik, Bourassa, & Hampton, 2009 ). For many women who did participate, high levels of support were required from the nurses to remind women of appointments and the Circle schedule, and to help them attend, given the difficult circumstances of their lives and their limited resources and poor health (e.g., over half had histories of head injuries and memory problems).…”
Section: Resultsmentioning
confidence: 99%
“…Elsewhere, we report on strategies to mitigate these limitations including further privileging Indigenous knowledge ( McKenzie, Varcoe, Browne, & Ford-Gilboe, 2018 ). Some women enrolled but were unable participate, reflecting the extreme economic deprivation and high levels of trauma many Indigenous women face ( Benoit et al, 2016 ; Daoud et al, 2013 ; Kubik, Bourassa, & Hampton, 2009 ). For many women who did participate, high levels of support were required from the nurses to remind women of appointments and the Circle schedule, and to help them attend, given the difficult circumstances of their lives and their limited resources and poor health (e.g., over half had histories of head injuries and memory problems).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, there was a higher prevalence of late and very late diagnosis among African, Caribbean, Black and Indigenous participants, with Indigenous individuals also more likely to be delayed presenters. Several Canadian studies have identified barriers to HIV testing and health care for these populations [32][33][34][35][36][37][38][39][40][41][42], and Ontario's recently released provincial HIV/ AIDS Strategy names both as priority populations for HIV testing campaigns that 'de-stigmatize testing . .…”
Section: Discussionmentioning
confidence: 99%
“…The stress-generation hypothesis further suggests that exposure to elevated life stressors and negative life events plays a role in predicting future sensitivity to stress and adverse health ( 22 ). Recurring or ongoing life-stressors, which include socio-economic and family strains ( 26 ), violence (including intimate partner violence) ( 13 , 27 ), as well as structural and socio-political factors ( 28 ) such as poverty ( 29 ), colonization ( 30 ), and heightened chronic stress due to gender inequity, racism, and homophobia ( 25 , 31 , 32 ), have been recognized as having a significant effect on poor physical and psychological health. As such, high, chronic psychological stress is an important contributor to the global disease burden, in particular for structurally marginalized communities ( 28 ) due to the high prevalence of life stressors, structural inequities, healthcare exclusion, and limited mental health and social supports ( 33 , 34 ).…”
Section: Introductionmentioning
confidence: 99%